Shotgun Johnny - Johnstone, William W.; Johnstone, J. A. (Pennacle Books, Kensington Publishing Corp., 2020)
It takes a brave man to ride shotgun for the Reverend's Temptation Gold Mine in the Sierra Nevada Mountains. It takes an even braver man to try to rob a coach of bullion when the shotgun rider is Johnny Greenway. Armed with his weapons of choice, Shotgun Johnny ain't stopping for no one ...